Management of Pathologic Fractures around the Knee: Part 1—Distal Femur - Martin, John R.; Auran, Richard L.; Duran, Michael D.; Comas, Amalia M. de; Jacofsky, David J. (The Journal of Knee Surgery, 2022)
Pathologic fractures secondary to metastatic disease are an increasingly prevalent problem. Such patients require multidisciplinary collaboration to optimize clinical outcomes. An established algorithm for clinical, laboratory, and radiographic work-up will ensure that each patient achieves the best outcome while avoiding catastrophic complications. Metastatic disease to the region of the knee is less commonly encountered than in other regions of the body, but it presents unique difficulties that merit discussion. Part one of this two-part article series will discuss the appropriate work-up of patients with suspected or impending pathologic fracture of the distal femur, highlight biopsy principles, address perioperative nonsurgical treatments that will optimize patient outcomes, and discuss available surgical treatment modalities.
Keywords: metastatic disease; femur; knee; orthopaedic oncology